Doing Identity in Luxembourg Subjective Appropriations - Institutional Attributions - Socio-Cultural Milieus (Kultur und soziale Praxis, 2011)
Luxembourg - international financial center, European administrative center, destination country for immigration? This empirical study provides insights about a society that has hitherto largely eluded scientific investigation and observes the processes of identity construction in globalised conditions. The interdisciplinary team of authors exposes the processes of subjective appropriations and institutional attributions at work in the fields of languages, spaces, perceptions of self and others as well as everyday cultures, and identifies for the first time socio-cultural milieus in the Grand Duchy. The findings of the three-year research project uncover the ambivalences and dynamics of a multicultural and multilingual society.